A 3-Year-Old Girl with Recurrent Infections and Autoimmunity due to a STAT1 Gain-of-Function Mutation: The Expanding Clinical Presentation of Primary Immunodeficiencies - Aldave Becerra, Juan Carlos; Cachay Rojas, Enrique (Frontiers in Pediatrics, 2017)
We report a 3-year-old Peruvian girl, born to non-consanguineous parents. At the age of 8 months she had a severe pneumonia complicated with empyema that required thoracic drainage and mechanical ventilation. Although no microorganisms were isolated, the patient recovered with broad-spectrum antibiotics. Since that date, she has presented multiple episodes of pneumonia and recurrent episodes of bronchospasm. At 1 year 5 months of age, the patient began with recurrent episodes of oropharyngeal, vaginal and skin candidiasis, which improved transiently after using oral azole drugs. At 2.5 years of age, she was admitted with lupus-like syndrome, including serositis, hemolytic anemia, thrombocytopenia, and positive antinuclear (1:80) and dsDNA (1:10) autoantibodies. Available immunologic testing was not contributory. Imaging studies revealed bilateral ethmoidal sinusitis and mild hepatomegaly. Bone marrow analysis did not showed evidence of leukemia or myelodysplasia, while renal biopsy concluded mild mesangial proliferation. Genetic studies revealed a pathogenic heterozygous STAT1 gain-of-function mutation (WT/P293L). The clinical status and lung function of the patient has worsened progressively. She has not achieved an optimal response to therapy, including high-dose intravenous immunoglobulin, GM-CSF, prophylactic antibiotics and antifungal drugs, so we plan to perform hematopoietic stem cell transplantation.